Flowering characteristics and breeding system of Deutzia parviflora - WANG Qi; LI Jinyu; WANG Xinyi; WANG Yixuan; GUO Wei; YUAN Tao (Xibei zhiwu xuebao)
[Objective] The study aims to examine the flowering and breeding characteristics of the native plant Deutzia parviflora, promote the resistance breeding and resource utilization of Deutzia as well as enrich the species of flowering shrubs in the northern region. [Methods] The morphological characteristics of flower organs, flowering phenology, pollen viability, stigma acceptability, and breeding system of D . parviflora were observed and analyzed. [Results] (1) D . parviflora began to bloom in late April and ended in mid-May in Beijing. Its flowering type is concentrated flowering, with a group flowering period of 22-23 d and a single flowering period of 8 d, which can be divided into 8 stages. (2) The stigma acceptability at the petal flattening stage was the strongest, and the pollen viability at the stamen expansion stage was the highest. (3) The optimal medium for pollen viability determination was: 100.0 g/L sucrose + 0.3 g/L H3BO3 + 0.2 g/L CaCl2. (4) Pollen can be dried and stored in the short term (within 10 d), at -20 ℃ and -80 ℃ in the medium term (10-30 d), and at -80 ℃ for a long time (more than 30 d). (5) The pollen-ovule ratio of D . parviflora was 23 695.93, the out-crossing index was 3, the fruit setting rate of xenogamy was the highest. [Conclusion] There is no apomixis in D . parviflora and the breeding system is a mixed mating system, dominanted by outcrossing mechanism, requiring pollinators, and it is more fertile and can be used as a parent for hybrid breeding in the genus Deutzia. Its low self-incompatibility is not due to dichogamy and herkogamy.